Voronoi diagrams for page segmentation - Gardella, Marina (2026)
Page segmentation is a key task in document processing, enabling effective extraction of structured information from diverse document types. This paper presents an in-depth analysis of the method proposed by Kise et al., a bottom-up approach using area Voronoi diagrams to identify spatial relationships between document parts. Our work provides a detailed description of the method, emphasizing clarity, reproducibility, and transparency, particularly regarding aspects not fully specified in the original paper. We highlight the impact of the parameter settings and preprocessing steps on the method’s performance. Through extensive testing, we demonstrate that the method can handle a wide range of layouts but exhibits notable sensitivity to specific document characteristics, especially in handling complex elements like handwritten text, lists, drop-caps, and tables.